Mediation of the association between screen time and suicidality by overweight/obesity and perceived overweight: results from the youth risk behavior surveillance system of the United States - Gao, Hong; Wang, Yifei; Wang, Xugang; Gao, Ming (Frontiers in Psychiatry, 2024)
Aim Adolescent suicide is a major public health concern, and modifiable risk factors associated with adolescent suicide remain poorly understood. This study aimed to assess the association between screen time and overweight/obesity and self-perceived overweigh and suicidality in adolescents. Methods Adolescents from the United States Youth Risk Behavior Surveillance System (YRBSS) between 2013 and 2019 were included in this cross-sectional study. The outcome was suicidality, including considered suicide, made a suicide plan, attempted suicide, and injurious suicide attempt. Multivariable logistic regression model was used to investigate the associations between screen time, overweight/obesity, self-perceived overweight, and suicidality, and expressed as odds ratio (OR) and 95% confidence interval (CI). Mediation analysis was used to explore the role of overweight/obesity and self-perceived overweight on the association between screen time and suicidality. Results A total of 30,731 adolescents were included, of which 6,350 (20.65%) had suicidality, including 5,361 (17.45%) with considered suicide, 4,432 (14.42%) with made a suicide plan, 2,300 (7.45%) with attempted suicide, and 677 (2.21%) with injurious suicide attempt. Adolescents with screen time ≥3h were related to higher odds of suicidality (OR=1.35, 95%CI: 1.23-1.46), overweight/obesity (OR=1.27, 95%CI: 1.19-1.38), and self-perceived overweight (OR=1.38, 95%CI: 1.30-1.48) after adjusting confounders. Adolescents with overweight/obesity (OR=1.30, 95%CI: 1.19-1.43) and self-perceived overweight (OR=1.54, 95%CI: 1.39-1.70) were associated with higher odds of suicidality. The association between screen time and suicidality was 4.67% mediated by overweight/obesity and 9.66% mediated by self-perceived overweight. Moreover, the mediating role of overweight/obesity was observed only in females, whereas there were no sex differences in the mediating effect of self-perceived overweight. Conclusion Both overweight/obesity and self-perceived overweight mediated the association between screen time and suicidality.